Rabbit model for in vivo study of anthracycline-induced heart failure and for the evaluation of protective agents - Simůnek, Tomás; Klimtová, Ivona; Kaplanová, Jana; Mazurová, Yvona; Adamcová, Michaela; Sterba, Martin; Hrdina, Radomír; Gersl, Vladimír (European journal of heart failure, 2004)
BACKGROUND: Cardiac toxicity associated with chronic administration of anthracycline (ANT) antibiotics represents a serious complication of their use in anticancer chemotherapy, but can also serve as a useful experimental model of cardiomyopathy and congestive heart failure. AIMS: In this study, a model of chronic ANT cardiotoxicity induced by repeated i.v. daunorubicin (DAU) administration to rabbits was tested. METHODS: Three groups of animals were used: (1) control group-10 animals received i.v. saline; (2) 11 animals received DAU (3 mg/kg, i.v.); (3) 5 animals received the model cardioprotective agent dexrazoxane (DEX, 60 mg/kg, i.p.), 30 min prior to DAU. All substances were administered once weekly, for 10 weeks. The DAU-induced heart damage and protective action of DEX were determined and quantitated with the use of histopathology, invasive haemodynamic measurements (e.g. left ventricular pressure changes-dP/dt(max), dP/dt(min)), non-invasive systolic function examinations (left ventricular ejection fraction, PEP/LVET index) and biochemical analysis of cardiac troponin T plasma concentrations. RESULTS: All the employed methods showed unambiguously pronounced heart impairment in the DAU group, with the development of both systolic and diastolic heart failure, as well as significant reduction of DAU-cardiotoxicity in DEX-pretreated animals. Other toxicities were acceptable. CONCLUSION: The presented model has been approved to be consistent and reliable and it can serve as a basis for future determinations and comparisons of chronic cardiotoxic effects of various drugs, as well as for the evaluation of potential cardioprotectants.
Keywords: Erythrocyte Indices; biologické markery; erytrocytární znaky; Models, Cardiovascular; Razoxane; Heart Failure; Daunorubicin; Antibiotics, Antineoplastic; srdeční komory; Myocytes, Cardiac; srdeční selhání; antracykliny; kardiomyocyty; vztah mezi dávkou a účinkem léčiva; razoxan; tepový objem; králíci; Anthracyclines; Dose-Response Relationship, Drug; Stroke Volume; protinádorová antibiotika; echokardiografie; myokard; Disease Models, Animal; Cardiovascular Agents; Biomarkers; kardiovaskulární látky; mužské pohlaví; zvířata; daunomycin; srdeční frekvence; Time Factors; Myocardium; Heart Ventricles; Rabbits; Animals; časové faktory; Male; tělesná hmotnost; modely nemocí na zvířatech; modely kardiovaskulární; Echocardiography; Heart Rate; Body Weight